Narrative Memory in Hyperfiction and Games - Barbas, Helena (2014)
The aim of this paper is to address some theoretical issues concerning the narrative practice in cyberspace. From a narratological perspective it intends to clarify the functioning of time and space in storytelling. For that purpose it traces the concept(s) of memory inherited from rhetoric; the use of memory as a narrative device in traditional accounts; the adaptations imposed by hyperfiction. Using practical examples (including two Portuguese case studies - InStory 2006, and Noon 2007) it will show how narrative memory strategies can be helpful in game literacy. The main purpose is to contribute to serious game research and (trans)literary studies.